Mechanisms of cross and multiple herbicide resistance in Alopecurus myosuroides and Lolium rigidum - Hall, L.M.; Tardif, F.J.; Powles, S.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Alopecurus myosuroides and Lolium rigidum have developed resistance to herbicides with several modes of action in many herbicide classes. A. myosuroides biotype Peldon A1 from England exhibits non-target site cross resistance to substituted urea and aryloxyphenoxypropionate herbicides (APP) due to enhanced metabolism. L. rigidum biotype SLR 31 from Australia has multiple resistance mechanisms, including both non-target site cross resistance and target site cross resistance. The majority of the SLR 31 population has enhanced metabolism of chlorsulfuron and diclofop-methyl and a mechanism correlated with altered plasma membrane response, which correlates with resistance to some APP and cyclohexanedione (CHD) herbicides. A small proportion of the population also has target site cross resistance to APP and CHD herbicides. While A myosuroides and L. rigidum share common biological elements, they are not unique. Non-target site cross resistance and multiple herbicide resistance is predicted to develop in other weed species. The repercussions of cross and multiple resistance warrant proactive measures to prevent or delay onset.